Sensibilidade ao glúten não celíaca em pacientes pediátricos: uma revisão da literatura - Vânia Gameiro de Carvalho; Nathalia Silva Queiroz (Sociedade Brasileira de Pediatria, 2022)
OBJECTIVE: This study aims to review the relevant bibliography about non-celiac gluten sensitivity in children and to summarize the main data of pathogenesis, symptomatology and diagnostic methods currently established, useful for clarifying the pediatric physician regarding this pathology. METHODS: The databases selected were: PubMed (The National Center for Biotechnology Information), LILACS (Latin American and Caribbean Health Sciences Literature) and SciELO (Scientific Electronic Library Online). Publications that contributed to the present review in the 2016-2021 interval, in English, Portuguese or Spanish, were chosen using the terms child, pediatrics, non-celiac gluten sensitivity and gluten sensitivity. RESULTS: Non-celiac gluten sensitivity occurs in patients in whom celiac disease and wheat allergy have been ruled out. Intestinal and extra-intestinal manifestations occur after eating gluten-containing foods and disappear after they are removed from the diet. The pathophysiological basis of non-celiac gluten sensitivity is related to the bodys innate immune response triggered by gluten peptides. The placebo-controlled double blind challenge test is considered the gold standard for diagnostic investigation, despite limitations. New methods are being tested in order to correctly affirm the diagnosis of non-celiac gluten sensitivity. CONCLUSION: The diagnostic determination of non-celiac gluten sensitivity is essential in order that the pediatric patient don't be subjected, unnecessarily, to gluten-free diets that can have a negative impact on their nutrition and development.